A study on the influence of dose rate on total ionizing dose effect of anti-fuse field programmable gate array—The irradiation damage is attenuated at low dose rate - Liu, Minqiang; Xu, Xianguo; Zeng, Chao; Xiong, Cen (Frontiers in Physics, 2022)
The influence of dose rate on the Total Ionization Dose (TID) effect of anti-fuse FPGA X1020B device was studied. The experimental results show that: 1) the total ionization dose irradiation failure of the FPGA does not originate from the input voltage decrease; 2) the lower the irradiation dose rate, the higher the TID failure threshold of the FPGA. Theoretical analysis shows that annealing effect plays a dominating role in the higher radiation hardness of the FPGA at low dose rate. And an analytical model of total ionization dose degradation effect of anti-fuse FPGA is established based on experimental data. The model can be used to rapidly predict the degradation degree of the anti-fuse FPGA at different irradiation doses of specific dose rates, which lays a foundation for scientific evaluation of radiation effect of anti-fuse FPGAs.